Taking the Temperature of Early Modern Studies: A Special Fiftieth Anniversary Issue of The Sixteenth Century Journal - Gibbs, Gary G. (The sixteenth century journal, 2019)
The article presents an introduction to the fiftieth anniversary issue of the journal.